2014
DOI: 10.5487/tr.2014.30.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhallation of e-Cigarette Cartridge Solution Aggravates Allergen-induced Airway Inflammation and Hyper-responsiveness in Mice

Abstract: Electronic cigarettes (e-cigarettes) are becoming increasingly popular worldwide and their cellular effects warrant further evaluation. In this study, we investigated the effects of an e-cigarette cartridge solution on allergen related asthmatic airway inflammation (AI) and airway hyperresponsiveness (AHR), when it is delivered by intratracheal route in mice. Asthmatic AI and AHR were induced by systemic sensitization to ovalbumin (OVA) followed by intratracheal, intraperitoneal, and aerosol allergen challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 26 publications
(32 reference statements)
0
88
1
5
Order By: Relevance
“…A simple explanation for the latter is that dysfunction of asthmatic smokers' small airways was less than this of COPD patients. It could also be a sign of increased bronchial hyperactivity since research in animal models has already showed that e-cigarette aggravates allergen-induced airway Inflammation and hyper-responsiveness 13 .…”
Section: Changes In Lung Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple explanation for the latter is that dysfunction of asthmatic smokers' small airways was less than this of COPD patients. It could also be a sign of increased bronchial hyperactivity since research in animal models has already showed that e-cigarette aggravates allergen-induced airway Inflammation and hyper-responsiveness 13 .…”
Section: Changes In Lung Functionsmentioning
confidence: 99%
“…There is also an increasing number of studies in animal models implicating possible health effects. Namely, exposure to e-cigarette vaping results in immunomodulatory effects that are similar to those observed after exposure to conventional cigarette smoke, impairs pulmonary anti-bacterial and anti-viral defenses 12 , aggravates allergen-induced airway Inflammation and hyper-responsiveness 13 , induces toxicity, and oxidative stress. The aforementioned studies indicate that e-cigarette use might have significant consequences on the human respiratory system.…”
Section: Introductionmentioning
confidence: 96%
“…2017). They have also been shown to induce an allergy‐based asthma inflammatory response (Lim and Kim 2014) and increased methacholine response (Larcombe et al. 2017), and increasing susceptibility of mouse lung cells to viral infection (Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Klinikai vizsgála-tokban a pára beszívását követő obstruktív hatások (légutak ellenállásának növekedése) megfeleltek a hagyományos cigaretta elszívása után tapasztaltaknak, ezért minden valószínűség szerint a hosszú távú használat során az e-cigaretta ugyanilyen elváltozásokat okozhat a tüdőfunkcióban [3,25]. Egyes vizsgálatok az allergiás asztma súlyosbodását írták le a pára hatására [26], más vizsgálatokban citokinek és gyulladásos mediátorok kiáramlását igazolták a tüdőszövetben [3,27].…”
Section: A Pára Egészségre Gyakorolt Hatásaiunclassified
“…Klinikai vizsgála-tokban a pára beszívását követő obstruktív hatások (légutak ellenállásának növekedése) megfeleltek a hagyományos cigaretta elszívása után tapasztaltaknak, ezért minden valószínűség szerint a hosszú távú használat során az e-cigaretta ugyanilyen elváltozásokat okozhat a tüdőfunkcióban [3,25]. Egyes vizsgálatok az allergiás asztma súlyosbodását írták le a pára hatására [26], más vizsgálatokban citokinek és gyulladásos mediátorok kiáramlását igazolták a tüdőszövetben [3,27].Az eddigi vizsgálatok alapján úgy tűnik, hogy az e-cigaretta használata során a kilélegzett párában jelen lévő részecskék minden, zárt térben tartózkodó személy egészségére ártalmasak [28]. Az aeroszol szállópor-koncentrációja meghaladja az Egészségügyi Világszervezet (WHO) hosszú távon elfogadható iránymutató határér-tékét [14], a szívre és tüdőre gyakorolt káros hatásain keresztül pedig növeli a halálozás kockázatát, valamint hozzájárul a nikotinfüggőség kialakulásához [29].…”
unclassified